LAND SUITABILITY ASSESSMENT FOR PATCHOULI (Pogostemon cablin) DEVELOPMENT AND ESSENTIAL OIL PRODUCTION - Adi Setiawan (BIOTROPIA, 2021)
The conformity of abiotic factors in the growing environment of crops determines the successful result of crop production. This study aims to assess and evaluate land suitability for plant growth and result of patchouli development in Dilem wilis, Bendungan Distric, Trenggalek Regency. The study was initiated with the survey and continued by utilizing analysis method to adjust the data with the criteria according to the classification of land suitability clashing and crops cultivation as indicator for assessing land suitability. The research was conducted on 3 locations from May to July 2017 for land suitability and from July to November 2017 for patchouli crops cultivation experiment. The result indicated from the three sampling Locations, specifically Location 1 presented the land suitability of N class, conforming that this Location was not suitable with the limiting factor of low K2O content of 0.08 me / 100 g. Meanwhile, both Location 2 and Location 3 presented similar land suitability class of S3s, tc, f, n conforming as less appropriate. The results of this study also depicted the influence of land suitability classes on plant growth; however, the difference in land classes (in this case S3 compared to N) did not demonstrate a correlation for oil yield and patchouli alcohol, where the element Potassium becomes a limiting factor.